Collaboration between a temperate phage and Pseudomonas aeruginosa quorum sensing constrains social cheats - Chen, Ruiyi; Traxler, Beth; Kropinski, Andrew M.; Greenberg, E. Peter (mBio, 2025)
Quorum sensing (QS) enables bacteria such as Pseudomonas aeruginosa to coordinate cooperative activities. How bacteria in cooperating groups can resist infiltration by non-cooperating variants is an emerging area of interest in sociobiology and molecular biology. There have been several recent reports on how QS and certain bacteriophage interact. In some strains of P. aeruginosa , QS can activate phage defense systems. At least one bacteriophage can repress P. aeruginosa QS. Here, we show that a previously undescribed bacteriophage can help cooperating groups of P. aeruginosa resist infiltration by non-cooperating QS mutants. This represents a mutualism in which both the bacteriophage and the P. aeruginosa host benefit at least under certain conditions.